Uma análise da política monetária brasileira no período 1999-2020 à luz da teoria quantitativa da moeda - Soares, Daniel Fachin (2022)
The Quantity Theory of Money is a fundamental part of the economic framework which, since its origin in the classical period, has played a role in the most diverse schools of economic thought. However, despite its wide acceptance and longevity – attributed above all to its explanatory capacity and coherence –, it is undeniable that part of its appeal stems from the simplicity and immediacy of its conclusions, more than from its explanatory power. Indeed, although QTM continues to be widely employed, the complete neutrality of money it states needs yet to be proved in several contexts, for example, with regard to the Brazilian economy throughout the 21st century. The results found in the present work point to a certain agreement between orthodoxy and heterodoxy on the invalidity of QTM for the national economy during the period 1999-2020. However, while the orthodoxy advocates a non-neutrality restricted to the short term, heterodoxy sees it as more pervasive and lasting. From the methodological perspective, the research described in the present work made use of both qualitative and quantitative analyses. Qualitative arguments were obtained from intensive theoretical research which included some major authors historically focused on the issue of the QTM. Arguments of a quantitative nature have resulted from empirical results calculated by this author or originated from third-party research, as obtained from extensive bibliographical researc